การพัฒนารูปแบบการจัดการศึกษานอกระบบโรงเรียนเพื่อเสริมสร้างทักษะการคิดวิจารณญาณในการป้องกันการเสพยาเสพติดสำหรับเยาวชนนอกระบบโรงเรียนในภาคใต้ - กรกฏ ไชยเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The objectives of this research were to 1) study state, problems, and needs to enhance critical thinking skills in drug addict prevention for non-formal education youth in the southern region of Thailand, 2) develop a non-formal education model to enhance critical thinking skills in drug addict prevention, 3) study the results of non-formal education model implementation; and 4) study the relevant factors that support and obstruct the implementation of the non-formal education model. This research used mix method approach. The research procedures were divided into 2 main stages: 1) the survey stage, studying the current state , problems and learning needs to enhance critical thinking skills in drug addict prevention for non-formal education youth in the southern region of Thailand from the sample groups of 360 non-formal education youth, 9 administrators, and 27 teachers; 2) the developmental stage involved designing a non-formal education model, studying the results of the quasi-experimental research from 40 non-formal education youth, using purposive sampling, divided into 20 subjects in experimental group and 20 subjects in the control group, studying the relevant factors that support and obstruct the implementation of the non-formal education model based on a focus group, and the 5 instruments used were (1) questionnaires for investigating state, problems, and needs, (2) questionnaires for surveying characteristics, (3) drug addicted knowledge tests, (4) critical thinking skills tests, and (5) interviewsThe results of the research were as follows:1. At the present state, more non-formal education youth involved in drugs. All sectors should play essential roles in preventing this group from drug addicts. The problems of non-formal education youth were that they had never developed critical thinking skills in drug addict prevention. Consequently, they needed to develop critical thinking skills in drug addict prevention; where as teachers and administrators were not interested and did not put priority in research and development on critical thinking skills.2. The results of the development of a non-formal education model consisted of six principles and a learning process to enhance critical thinking skills. The model included: 1) objectives based on the state, problems, and needs, 2) content structures emphasized facilitators’ potential, thinking process, drugs, and self-esteem; 3) a learning process which conducted activities as steps planned; 4) learning resources and materials were based on contents; 5) measurement and evaluation were from authentic assessment; 6) facilitators, researchers and learners were friendly.3. The results of the model implementation showed that the experimental group, who learned from using the non-formal education model, scored significantly higher than the control group at the significance level of .05 in the three aspects, included drug addicted knowledge, characteristics, and critical thinking skills.4. The factors and provision affecting the non-formal education model implementation were 1) purposes were clear and appropriate to learners, 2) content was meaningful and realistic, 3) process put students’ priority, knowledge was able to be directly applied, and activities were continuously and easily understood 4) measurement and evaluation had easily understandable questions and flexible according to time gained 5) learning resources and learning environment were not difficult, 6) facilitators and researcher understood the problems and the ways to solve them and had potential and positive attitudes, learners were willing to learn, enjoyable and relaxed.